Opening a Performance Dialogue With Employees: Facework, Voice, and Silence. (October 2015) - Kingsley Westerman, Catherine Y.; Smith, Sandi W.
This study examines how a supervisor's delivery of negative feedback affects employees' tendency to respond by either voicing their ideas or remaining silent. The results show that approbation, or the use of praise to soften face threat, was the most effective facework message for the supervisor to use when providing negative feedback. When employees felt more threatened, they reported that they would be less likely to use voice to help others and more likely to use silence defensively as a response, but as their perceptions of threat decreased, they generally reported that they were more likely to use voice to help others. The article discusses implications of these results, limitations of the study, and future directions of this research.